2021
DOI: 10.1080/01584197.2021.1922293
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological relationships of fieldwrens (Calamanthus): implications for conservation status and management

Abstract: Appendix S1. Summary of the major historical taxonomic treatments of Calamanthus sensu stricto, using the nomenclature of Schodde and Mason (1999), who recognised three species: C. montanellus (0 subspecies), C. campestris (7) and C. fuliginosus (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The papers in this Emu Austral Ornithology special issue -Conservation Genetics: Showcasing Applications in Austral Birds -clearly demonstrate that genetic data can inform conservation efforts in myriad ways. From delineating conservation management units and revising taxonomy (Burbidge et al 2021;Grosser et al 2021;Joseph et al 2020;, to examining population structure and connectivity within species (Beckmann et al 2021;Brown et al 2021;Lohr et al 2020;Taylor et al 2021;Wold et al 2021), to informing translocation management (Bolton et al 2021;Cowen et al 2021;Dwyer et al 2021;Taylor et al 2021), to understanding better the life histories of threatened species (Forsdick et al 2021), to using genetic data to infer past and future extinctions (Cowles et al 2021;Grosser et al 2021;Ramstad et al 2021), through to landscape-level longitudinal studies across multiple species (Radford et al 2021), we have shown that genetics is a powerful tool that should be in every conservation manager's toolbox.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The papers in this Emu Austral Ornithology special issue -Conservation Genetics: Showcasing Applications in Austral Birds -clearly demonstrate that genetic data can inform conservation efforts in myriad ways. From delineating conservation management units and revising taxonomy (Burbidge et al 2021;Grosser et al 2021;Joseph et al 2020;, to examining population structure and connectivity within species (Beckmann et al 2021;Brown et al 2021;Lohr et al 2020;Taylor et al 2021;Wold et al 2021), to informing translocation management (Bolton et al 2021;Cowen et al 2021;Dwyer et al 2021;Taylor et al 2021), to understanding better the life histories of threatened species (Forsdick et al 2021), to using genetic data to infer past and future extinctions (Cowles et al 2021;Grosser et al 2021;Ramstad et al 2021), through to landscape-level longitudinal studies across multiple species (Radford et al 2021), we have shown that genetics is a powerful tool that should be in every conservation manager's toolbox.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, different species or units show little morphological variation or, conversely, a phenotypic trait is extremely plastic, leading to great differentiation within a species or unit (Dussex et al 2018). Four papers in this special issue demonstrate the advantage of using phenotypic data in tandem with genetic data and phylogenetic approaches to provide a stronger framework to help inform conservation management (Burbidge et al 2021;Grosser et al 2021;Joseph et al 2020;. Grosser et al (2021) showcase the use of genetic data in delineating taxa or conservation units previously described based on morphology alone.…”
Section: Conservation Units and Taxonomymentioning
confidence: 99%
See 2 more Smart Citations